Factors Associated With Scabies In Boarding Students In SMKN AgricultureIntegrated Riau Province In 2019 - alhidayati yati; Syukaisih .; Risa Amalia; Indra Sukma (Public Health Department, Faculty of Health Science University Muhammadiyah Bengkulu, 2020)
Scabies or can be known as scabies is eruption skin caused by investment and sentiment by the sarcoptes scabiei varhominis lice and gives rise to clinical symptoms, such as popular lesions, pustules, vesiclen, sometimes erosion and crusting, and gray tunnels accompanied by very itchy complaints on the skin folds based on the initial survey on intergrated agricultural, Riau Province there were 6 students affeceted by scabies the prevelance of scabies in Indonesia according to the Indonesia ministry of health data from health centers throughaout Indonesia in 2015, incedence of scabies ranks third of the 12 most common skin disease, curently the incedence increase higher from 20 years ago. The aim of the researchers was to independent and dependent variables namely knowledge, personal hygiene, attitudes, clothes hygiene and the role og UKS officer findout the factors associated with scabies in the integrated SMKN Agricultur Vocational School of Riau Province,while the type of this study wa quatitative analytic with sectional design, with a total sampel of 147 people. The sampling technique used ti take samples was total sampling, namely overall, research results. Showed a relationship between knowledge (P value = 0,026) POR = 2,400 ( CI 95%, 1,165-4,946), personal hygiene (P value = 0,018) POR = 2,711 (CI 95%, 1,242-5915), attitude (P value = 0,046) POR = 2,188 (CI 95%, 1,071-4,468), clothes hygiene (P value = 0,43) POR = 2,165 (CI 95%, 1,1079-4,344), the role of UKS (P value = 1,000) with the incidence of scabies in boarding students. It is suggested ti the teacher or health personnel to pay attetion to health in the school eviroment, we can do it by improving students knowledge by providing information.